Comparing visual acuity, range of vision and spectacle independence in the extended range of vision and monofocal intraocular lens. (21st May 2018) - Hogarty, Daniel T; Russell, Deborah J; Ward, Bernadette M; Dewhurst, Nicholas; Burt, Peter
Abstract: Importance: This study is the first to compare the extended range of vision (ERV) intraocular lens (IOL) targeted at micro‐monovision to a monofocal targeted at binocular emmetropia. Background: Compares visual acuity, range of vision and spectacle independence in monofocal and ERV IOLs. Design: Assessor‐blinded retrospective cohort study. Participants: Eighty‐eight participants (176 eyes) with bilateral IOL implants at 5+ month postoperative review. Methods: Regression analyses (general estimating equations and multiple linear regression) tested associations between IOL type (ZA9002 Tecnis 3‐piece or Tecnis ZCT monofocal; and Tecnis Symfony ERV IOL) and visual acuity, adjusting for key confounders including residual astigmatism. Main Outcome Measures: Monocular and binocular visual acuity measured with and without distance refractive correction at distance (3.00 m), intermediate (1.00 and 0.63 m) and near (0.40 m) (logMAR units); near vision reading test used British 'N' notation; self‐reported spectacle independence. Results: There was no significant difference between ERV and monofocal groups in uncorrected binocular visual acuity at distance ( P = 0.595). Binocular uncorrected visual acuity at intermediate (0.63 m: monofocal 0.24, ERV 0.09, P < 0.001) and near (0.40 m: monofocal 0.42, ERV 0.18, P < 0.001) were significantly better in the ERV group. Binocular uncorrected near vision: all the ERV group read N8 or better, compared to 36% in the monofocal group ( P < 0.001); 93% of the ERV group reported spectacle independence at near compared to 33% in the monofocal group ( P < 0.001). Conclusions and Relevance: The ERV IOL, targeted to achieve micro‐monovision, demonstrated superior range of visual acuity and spectacle independence compared to the monofocal targeted to achieve emmetropia.